Engaging faith communities in public health messaging in response to COVID-19: Lessons learnt from the pandemic in Ituri, Democratic Republic of Congo - Baba, Amuda; Grant, Liz; Pearson, Nigel; Wild-Wood, Emma; Falisse, Jean-Benoit; Way, Yossa; Kangamina, Sadiki (Frontiers in Public Health, 2022)
The article describes a series of challenges faced by faith leaders in the Democratic Republic of Congo (DRC) in engaging with current public health strategies for the COVID-19 pandemic. It explores why long-standing collaborations between government, faith-based health services and leaders of faith communities had limited impact. It identifies novel approaches to develop effective health communication that resonates with local communities. Methods Opinions of faith leaders in the provinces of Ituri and Nord-Kivu in the Democratic Republic of Congo (DRC) were sought through a workshop using a qualitative participatory research design. A topic guide to frame the conversation was developed from data gathered in prior qualitative interviews of faith leaders and members. Perspectives from differing faiths were curated and emerging themes identified and shared to produce a co-created case study for change. Findings Local faith leaders described how misinterpretation and misinformation about COVID-19 and lack of clarity about given public health measures led to public confusion. Leaders described a lack of capacity to do what was being asked by government authorities in response to the public health measures. Leaders identified that their knowledge of faith communities’ concerns was not sought, and identified the value of setting messages in a language that resonated with the worldview and faith beliefs of their congregations. They recognised that they had no training to formulate health messages, which they saw as a missed opportunity for improved health outcomes. Faith leaders spoke of their commitment and desire to co-create public health messages with health officials for more effective health promotion. Conclusion Public trust in faith leaders is crucial in health emergencies. The initial request by government authorities for faith leaders to deliver set health messages rather than co-develop and design messages appropriate for their congregations resulted in faith communities failing to understand health messages. Co-creation of health messages with stakeholders using language familiar to faith communities could help to ensure more effective public health communication and counter misinformation.